Cover Feature: Insulating Polymer‐Hydrogel Nanocomposite Thin Film ‐ Based Catalytic Electrode for Efficient Oxygen Evolution Reaction (ChemElectroChem 7/2019). Issue 7 (6th March 2019) - Divya Madhuri, U.; Radhakrishnan, T. P.
Abstract : The Cover Feature shows an insulating polymer–semiconductor nanocomposite thin film used as an electrocatalyst for water oxidation. The critical role of polymer swelling in aqueous electrolyte is highlighted. More information can be found in the Communication by U. Divya Madhuri and T. P. Radhakrishnan onpage 1984 in Issue 7, 2019 (DOI:10.1002/celc.201801659 ).